2006
DOI: 10.1007/s00213-006-0577-y
|View full text |Cite
|
Sign up to set email alerts
|

The drug-induced helplessness test: an animal assay for assessing behavioral despair in response to neuroleptic treatment

Abstract: After discussing potential alternative interpretations of the drug-induced changes of EFs, we propose the DH test as a useful test for assessing a drug-induced, depressive-like state that may contribute to neuroleptic dysphoria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Previous studies using preclinical animal models to detect antidepressant-like effects in atypical antipsychotics have been challenging, and atypical antipsychotics are known to be clinically useful for treating symptoms in patients with major depression or bipolar depression. Indeed, a previous report using the learned helplessness paradigm (Ballard et al, 2007) demonstrated that haloperidol, risperidone, olanzapine, and aripiprazole aggravated depressive behavior, whereas quetiapine showed no effect. As a result, it has been proposed that the learned helplessness paradigm may be a model for evaluating antipsychotic-induced dysphoria but not for evaluating the antidepressant effects in antipsychotics.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies using preclinical animal models to detect antidepressant-like effects in atypical antipsychotics have been challenging, and atypical antipsychotics are known to be clinically useful for treating symptoms in patients with major depression or bipolar depression. Indeed, a previous report using the learned helplessness paradigm (Ballard et al, 2007) demonstrated that haloperidol, risperidone, olanzapine, and aripiprazole aggravated depressive behavior, whereas quetiapine showed no effect. As a result, it has been proposed that the learned helplessness paradigm may be a model for evaluating antipsychotic-induced dysphoria but not for evaluating the antidepressant effects in antipsychotics.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that D2R density is significantly decreased in the core of the nucleus accumbens and in the medial and lateral caudate nuclei in rats that became "helpless" after the LH training [15]. D2R agonists have been shown to significantly decrease the number of escape failures after the LH training, whereas D2R antagonists have the opposite effect [1,34]. Also, tricyclic antidepressants that increase dopaminergic activity reverse the escape deficit produced by the LH training in rats, and D2R antagonists were shown to suppress the behavioral effect of tricyclic antidepressants in the LH paradigm [2,34].…”
Section: Discussionmentioning
confidence: 99%
“…First, if the behavioral phenotypes observed in the mutant are the consequence of increased expression of D2S, then D2S would have a functional effect opposite to that of D2L. As described previously, blockade of D2R using pharmacological agents increases the escape deficits in the LH paradigm in normal rodents [1,2,34]. The fact that mice lacking D2L displayed the enhanced escape deficits in LH paradigm suggested that the deficiencies were likely attributed to the lack of D2L; otherwise the reverse behavioral phenotype would be predicted.…”
Section: Discussionmentioning
confidence: 99%
“…In Study 2, rats received cumulative increasing doses of morphine (3.75, 15 and 22.5 mg/kg), morphine + quetiapine (3.75 + 3, 15 + 10 and 22.5 + 30 mg/kg) or vehicle. The chosen doses were based on previous studies 15–19 and a pilot study with three rats before the start of both Studies 1 and 2. Intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%